2020
DOI: 10.21203/rs.3.rs-26682/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Ligustrazine Nanoparticles on Th1/Th2 Balance by TLR4/MyD88/NF-κB Pathway in Rats with Postoperative Peritoneal Adhesion

Abstract: Background Postoperative peritoneal adhesion (PPA) is regarded as fibrous bands connecting both injured abdominal wall and organs or adjacent tissues and associated with T helper (Th)1 and Th2 differentiation. However, the critical role of immunopathogenesis of adhesion formation was precisely unknown. Previously we demonstrated that ligustrazine have positive effects on adhesion formation. And microarray analysis revealed TLR4/MyD88/NF-κB pathway as an important underlying regulatory mechanism in the onset a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Loading capacity and entrapment efficiency are two pivotal indicators to measure the properties of nanoparticles. The PLA nanoparticles loaded with ligustrazine had high loading capacity and entrapment efficiency, as we reported previously [25]. It also had uniform spherical morphology with a smooth surface and good dispersivity (Figure 11(a)).…”
Section: Ln Attenuates Peritoneal Adhesion In Ppa Rats Bysupporting
confidence: 73%
See 3 more Smart Citations
“…Loading capacity and entrapment efficiency are two pivotal indicators to measure the properties of nanoparticles. The PLA nanoparticles loaded with ligustrazine had high loading capacity and entrapment efficiency, as we reported previously [25]. It also had uniform spherical morphology with a smooth surface and good dispersivity (Figure 11(a)).…”
Section: Ln Attenuates Peritoneal Adhesion In Ppa Rats Bysupporting
confidence: 73%
“…The distribution of particle size is about 200 nm. And LN had stable and sustained release behavior, evidenced by the in vitro drug release assay [ 25 ]. The outstanding features of LN are the prominently sustained release effect and good stability for tissue penetration via a positive targeting mechanism, which may be a novel agent for preventing PPA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Activation of M1-type microglia is a common phenomenon [8], and their production of pro-inflammatory factors, such as TNF-α, IL-6, IL-12, and IL-1β, has the potential to cause damage to neuronal cells or even to trigger death, but at the same time, it also leads to an increase in the activity of the microglia that thereby triggering the development of PD, creating a continuous vicious cycle. One study found that the expression levels of TLR4, NF-Κb, p65, and p38MAPK were significantly increased in the brain of Parkinsonian rats [9]. The expression of these substances can be significantly reduced by using tensin, and furthermore, the expression and decline of these substances become greater with the increase of tensin dose.…”
Section: Therapeutic Mechanism Of Gastrodia Elata In Pd 21 Reduce Neu...mentioning
confidence: 99%